The “Death or Freedom” Dilemma in Armenian Identity - Zakaryan, Seyran (Bulletin of Yerevan University E: Philosophy, Psychology, 2018)
By showing the examples of “Death or Freedom” dilemma among Armenians, the author thinks, that the Armenian historical-political thought, without taking into consideration the results of historical events, almost equalized the strive for independence through battle, at the cost of blood and martyrdom with national liberation battle. The other option of reaching the goal through peaceful, bloodless and diplomatic ways was not appreciated (with few exceptions), was neglected, frequently was criticized from the scratch and sometimes was identified with betrayal. Based on this, daily and historical-theoretical thought processed the mythical, epic and historical materials in such a way, that one of the options of “Freedom and death” dilemma (giving preference to armed fighting) was not only justified but also canonized. Armenian thought justified the necessity and inevitability of armed fighting, created a myth that armed resistance and achieving freedom at the cost of death is almost the only legal way of keeping identity. Based on this approach the criteria of differentiating the national heroes and traitors, stereotypes and mental patterns of presenting and covering history were formulated.
Keywords: “Death or Freedom”, Armenian identity, legend of Haik and Bel, lpic, freedom, independence, archetype, Hero, irrational victory